ANALYSIS OF PHYSICAL EDUCATION IN ENHANCING CHILDREN'S MOTOR SKILLS - Putri, Prillya Komala (Jurnal Pendidikan, Kesehatan dan Olahraga, 2024)
Sports education plays a crucial role in enhancing children's motor skills, encompassing both gross and fine motor abilities. Through structured and enjoyable physical activities, sports education helps children develop coordination, balance, muscle strength, and body flexibility. Gross motor skills, such as running, jumping, and playing ball, as well as fine motor skills, like catching small balls or writing, can be improved through appropriate exercises. Beyond physical benefits, sports education also contributes to psychological aspects, including confidence, social skills, and teamwork. Therefore, sports education not only focuses on physical development but also positively impacts children’s social and emotional growth. This study aims to analyze how sports education enhances children’s motor skills and provides a deeper understanding of the importance of physical activities in children's developmental stages.